2018
DOI: 10.1128/jvi.01546-17
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Escape of Human Astrovirus from Antibody Neutralization: Broad Implications for Rational Vaccine Design

Abstract: Human astroviruses are recognized as a leading cause of viral diarrhea worldwide in children, immunocompromised patients, and the elderly. There are currently no vaccines available to prevent astrovirus infection; however, antibodies developed by healthy individuals during previous infection correlate with protection from reinfection, suggesting that an effective vaccine could be developed. In this study, we investigated the molecular mechanism by which several strains of human astrovirus serotype 2 (HAstV-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Likewise, residues after K187 in the C-terminal region of the CCD also appear to be flexible. Thus, RSV G is part of a growing list of antigens with flexible or intrinsically disordered regions (IDRs) that are targeted by antibodies (48)(49)(50)(51)(52)(53)(54)(55)(56). The observation of different conformations of the RSV G CCD raises several important questions.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, residues after K187 in the C-terminal region of the CCD also appear to be flexible. Thus, RSV G is part of a growing list of antigens with flexible or intrinsically disordered regions (IDRs) that are targeted by antibodies (48)(49)(50)(51)(52)(53)(54)(55)(56). The observation of different conformations of the RSV G CCD raises several important questions.…”
Section: Discussionmentioning
confidence: 99%
“…HAstV serotype 8 strain Yuc8 was isolated in our laboratory. All viral strains were activated with trypsin and grown as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…Humoral immunity plays an important role in protecting against AstVs since the presence of protective antibodies against HAstV in healthy adults provides a mechanism of protection against reinfection [46,47]. The development of anti-AstV therapies is hampered by the gap in knowledge of protective antibody epitopes on the AstV capsid surface [48] and the immunosuppressing peptides along AstV CP [46,49,50]. Most of AstV vaccine research studies, including our previous study, have been focused on the full-length CP vaccine candidates, which all showed partial unsatisfactory immunity [36,37,51].…”
Section: Discussionmentioning
confidence: 99%